2018
DOI: 10.1167/tvst.7.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Objective Evaluation of Visual Fatigue Using Binocular Fusion Maintenance

Abstract: PurposeIn this study, we investigated whether an individual's visual fatigue can be evaluated objectively and quantitatively from their ability to maintain binocular fusion.MethodsBinocular fusion maintenance (BFM) was measured using a custom-made binocular open-view Shack–Hartmann wavefront aberrometer equipped with liquid crystal shutters, wherein eye movements and wavefront aberrations were measured simultaneously. Transmittance in the liquid crystal shutter in front of the subject's nondominant eye was red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…BFM is more easily collapsed using binocular stress in patients with IXT than in healthy individuals (Figs 3-5 and Tables 2 and 3). The present findings are in agreement of those reported by Hirota et al [11], who reported that BFM in the healthy volunteers was significantly reduced and fusional vergence range was not significantly different using binocular stress, suggesting that the BFM test can also be applied to patients with IXT.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…BFM is more easily collapsed using binocular stress in patients with IXT than in healthy individuals (Figs 3-5 and Tables 2 and 3). The present findings are in agreement of those reported by Hirota et al [11], who reported that BFM in the healthy volunteers was significantly reduced and fusional vergence range was not significantly different using binocular stress, suggesting that the BFM test can also be applied to patients with IXT.…”
Section: Discussionsupporting
confidence: 94%
“…The eye position data collected during the 50 s measurement periods were averaged over the three trials before and after the visual task. The binocular fusion break time (T B ) was calculated automatically from the nondominant eye movements based on the results of our previous study [11] using Python 3.6.5. Base min was determined as the average eye position over 2 seconds after beginning the measurement in which the transmittance of the liquid crystal shutter remained equal between the right and left eye.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations